“Ingsung Titip Tajug Lan Fakir Miskin” Budaya Mentifak Etnik Cirebon Dikaji Dari Dimensi Etnopedagogi - Mauly Rahadiani; Aninda Utari Pertiwi; Fitriani Tri Rahayu; Iin Wariin Basyari; Auliya Aenul Hayati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study aims to identify the values of local wisdom in the mentifact culture of the Cirebon Ethnic saying "ingsun titip tajug lan fakir miskin". The research used a qualitative method.  Data were collected or extracted using open interview techniques, documentation studies and direct observation of Cirebon cultural heritage sites. Informants include, Cirebon cultural figures, education figures and Cirebon community leaders. The data validation uses triangulation techniques. Triangulation is an approach taken by researchers to explore and perform qualitative data processing techniques. The research resulted in the conclusion that; the expression petatah petitih Cirebon contains local wisdom values; (1) the value of faith and devotion to God Almighty; (2) social values and togetherness, (3) the value of responsibility, and (4) the value of mutual cooperation. These values can be used as learning materials and resources through an ethnopedagogical approach in elementary schools. Recommendations that the expression of petatah petitih 'ingsun titip tajug lan fakir miskin' can be implemented into culture-based learning in the Cirebon ethnic community as an effort to preserve local culture.